Acetylcholinesterase alterations reveal the fitness cost of mutations conferring insecticide resistance - Tang Zhen; Frémaux Isabelle; Alies Carole; Lougarre Andrée; Shi Ming; Stojan Jure; Fournier Didier (BMC Evolutionary Biology, 2004)
Abstract Background Insecticide resistance is now common in insects due to the frequent use of chemicals to control them, which provides a useful tool to study the adaptation of eukaryotic genome to new environments. Although numerous potential mutations may provide high level of resistance, only few alleles are found in insect natural populations. Then, we hypothesized that only alleles linked to the highest fitness in the absence of insecticide are selected. Results To obtain information on the origin of the fitness of resistant alleles, we studied Drosophila melanogaster acetylcholinesterase, the target of organophosphate and carbamate insecticides. We produced in vitro 15 possible proteins resulting from the combination of the four most frequent mutations and we tested their catalytic activity and enzymatic stability. Mutations affected deacetylation of the enzyme, decreasing or increasing its catalytic efficiency and all mutations diminished the stability of the enzyme. Combination of mutations result to an additive alteration. Conclusion Our findings suggest that the alteration of activity and stability of acetylcholinesterase are at the origin of the fitness cost associated with mutations providing resistance. Magnitude of the alterations was related to the allelic frequency in Drosophila populations suggesting that the fitness cost is the main driving force for the maintenance of resistant alleles in insecticide free conditions.